Factors Related to Rehospitalization in Patients with Congestive Heart Failure - Selvi Lestari; Hendra Kusumajaya; Rizky Meilando (Genius Journal, 2027)
Introduction:  Congestive Heart Failure (CHF) is a complex clinical syndrome characterized by a decline in functional capacity, often resulting in recurrent rehospitalization. The rehospitalization rate has been steadily increasing at Bakti Timah Hospital Pangkalpinang. Factors such as hypertension, non-adherence to dietary recommendations, and low quality of life contribute to rehospitalization among CHF patients. Objective: This study aimed to identify factors associated with rehospitalization among CHF patients at Bakti Timah Hospital Pangkalpinang in 2025. Method : This research employed a quantitative approach with a cross-sectional survey design. The population consisted of all CHF patients undergoing treatment at the hospital, with a total of 59 respondents selected using purposive sampling. Result: The results revealed significant associations between a history of hypertension (p=0.01; POR=7.031; 95% CI: 2.222–22.254), dietary adherence (p=0.003; POR=6.000; 95% CI: 1.935–18.603), and quality of life (p=0.017; POR=4.267; 95% CI: 1.420–12.824) with rehospitalization events Conclusion:  In conclusion, a history of hypertension, dietary adherence, and quality of life are important factors influencing rehospitalization among CHF patients. Enhancing patient and family understanding of hypertension management, implementing appropriate dietary practices, and improving quality of life are expected to help reduce the rehospitalization rate